CORPORATE GOVERNANCE AND COMPANY’S VALUE: MODERATING ROLE OF ENTERPRISE RISK DISCLOSURE AMONG LISTED BANKS IN INDONESIA - Nadia Ersy Mithasari; H. Akram; Siti Aisyah Hidayati (Malete Journal of Accounting and Finance)
Banking cases in Indonesia are often colored by various cases, ranging from those involving theft of customer funds, corruption, embezzlement, and fraud, most of which are carried out by individuals and bank officials themselves. This is contrary to the concept of a bank that guarantees a sense of security and trust to its customers. This research seeks to evaluate the impact of effective corporate governance on company value, using corporate risk management disclosure as a moderating variable. This study employs a quantitative research approach using a census technique. The research sample included 43 banking firms listed on the Indonesia Stock Exchange from 2019 to 2023. The results of this study indicate that good corporate governance has a coefficient value of -582.98 with a p-value of 0.6276, this indicates an insignificant negative effect on company value. Company value is not determined by the good corporate governance rating represented by the composite value. In this case, there is asymmetric information between the principal and the agent, where information regarding the implementation of good corporate governance tends not to be utilized or not used by external parties and other interested parties in making investment decisions. Then, Enterprise risk management disclosure cannot moderate the effect of good corporate governance on company value. indicated by a coefficient value of 5.83 and a p-value of 0.6438. The wider the ERM information disclosed, the company value will decrease, this is because the breadth of information disclosed by the company about ERM management is perceived as negative news (bad news) by investors because information related to risks disclosed in the financial statements has not been fully followed by complete information related to how the company anticipates or mitigates these risks.